International nonproprietary names for monoclonal antibodies: an evolving nomenclature system. Issue 1 (31st December 2022) - Guimaraes Koch, Sofia S.; Thorpe, Robin; Kawasaki, Nana; Lefranc, Marie-Paule; Malan, Sarel; Martin, Andrew C.R.; Mignot, Gilles; Plückthun, Andreas; Rizzi, Menico; Shubat, Stephanie; Weisser, Karin; Balocco, Raffaella
ABSTRACT: Appropriate nomenclature for all pharmaceutical substances is important for clinical development, licensing, prescribing, pharmacovigilance, and identification of counterfeits. Nonproprietary names that are unique and globally recognized for all pharmaceutical substances are assigned by the International Nonproprietary Names (INN) Programme of the World Health Organization (WHO). In 1991, the INN Programme implemented the first nomenclature scheme for monoclonal antibodies. To accompany biotechnological development, this nomenclature scheme has evolved over the years; however, since the scheme was introduced, all pharmacological substances that contained an immunoglobulin variable domain were coined with the stem - mab . To date, there are 879 INN with the stem - mab . Owing to this high number of names ending in - mab, devising new and distinguishable INN has become a challenge. The WHO INN Expert Group therefore decided to revise the system to ease this situation. The revised system was approved and adopted by the WHO at the 73 rd INN Consultation held in October 2021, and the radical decision was made to discontinue the use of the well-known stem - mab in naming new antibody-based drugs and going forward, to replace it with four new stems: - tug, -bart, -mig, and - ment .